OPTIMIZATION OF THE SUPPLY CHAIN IN COMMERCIAL LOGISTICS: IMPACT ON EFFICIENCY AND PROFITABILITY - ZAVADSKA, Olena; MISIUKEVYCH, Valentyna; SYSOIEV, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In modern conditions, when the activities of companies are constantly influenced by external factors, the efforts of top management are mainly aimed at the maximum optimization of activities, as a basis for ensuring its efficiency and profitability. The article analyzes the prerequisites for updating the issue of supply chain optimization. The essence of the supply chain optimization category was studied, the problem areas with which it is connected were systematized in terms of such components as stocks, risks, demand, expectations. The phases of supply chain optimization, which include design, planning and execution stages, are developed and graphically presented. The need to track key indicators of the supply chain is established and the most informative of them are displayed, namely: picking and packing time, cash-to-cash time cycle, inventory turnover, gross return on investment, delivery timeliness indicator, delivery terms and reasons for returns. A parallel has been drawn between theoretical developments and the practice of their implementation on the device of Ukraine in the conditions of a pandemic and war. Measures that have a positive effect on the optimization of the supply chain using innovative warehouse and routing technologies have been identified. The criteria for optimizing the supply chain were studied. The methods used to optimize the supply chain in modern conditions are considered. Reference models of supply chain management were analyzed and their role in the process of optimization of such chains was determined. A parallel has been drawn between theoretical developments and the practice of their implementation on the device of Ukraine in the conditions of a pandemic and war. The measures that have a positive effect on the optimization of the supply chain, as well as the software that is used for these purposes and allows to significantly increase its efficiency, have been identified. Further prospects for exploration in the direction of research are outlined.